Clinically and pharmacologically relevant interactions of antidiabetic drugs. (April 2016) - May, Marcus; Schindler, Christoph
Patients with type 2 diabetes mellitus often require multifactorial pharmacological treatment due to different comorbidities. An increasing number of concomitantly taken medications elevate the risk of the patient experiencing adverse drug effects or drug interactions. Drug interactions can be divided into pharmacokinetic and pharmacodynamic interactions affecting cytochrome (CYP) enzymes, absorption properties, transporter activities and receptor affinities. Furthermore, nutrition, herbal supplements, patient's age and gender are of clinical importance. Relevant drug interactions are predominantly related to sulfonylureas, thiazolidinediones and glinides. Although metformin has a very low interaction potential, caution is advised when drugs that impair renal function are used concomitantly. With the exception of saxagliptin, dipeptidyl peptidase-4 (DPP-4) inhibitors also show a low interaction potential, but all drugs affecting the drug transporter P-glycoprotein should be used with caution. Incretin mimetics and sodium–glucose cotransporter-2 (SGLT-2) inhibitors comprise a very low interaction potential and are therefore recommended as an ideal combination partner from the clinical–pharmacologic point of view.